Men in (Shell-)Shock: Masculinity, Trauma, and Psychoanalysis in Rebecca West's The Return of the Soldier - Misha Kavka (Studies in 20th & 21st Century Literature, 1998)
This paper undertakes to read Rebecca West's first novel, The Return of the Soldier (1918), as a critical exploration of masculine trauma on the one hand and an ambivalent engagement with Freudian psychoanalysis on the other. The novel proves interesting as a site in which two shifting cultural contexts intersect: the wartime culture of England facing the "shell shock" of its men, and the contemporaneous infusion of English intellectual culture with psychoanalytic ideas. Though the effects of new war technology and "a newer kind of doctor," West challenge existing notions of stable masculinity, West maintains that masculinity has all along been simply a construct, a shell built around inarticulable trauma. The fact that in this novel West, despite her early pugnaciously feminist journalism, remains as much within the masculine order as critical of it forces us to expand our notions of the forms feminist narrative can take. This paper argues that the novel is a feminist narrative in the sense that it positions masculine trauma as a mark of adherence to the social order for both men and women.
Keywords: Rebecca West; The Return of the Soldier; exploration; masculine trauma; trauma; ambivalent; engagement; Freudian psychoanalysis; cultural context; wartime; England; shell shock; men; English intellectual culture; psychoanalytic; new war technology; new kind of doctor; stable masculinity; challenge; masculinity; construct; feminist journalism; feminist narrative; social order; women